Closed form models for dwell point locations in a multi–aisle automated storage and retrieval system. (10th April 2015) - Hale, Trevor S.; Hanna, Michael E.; Huq, Faizul; Gil, Adrian
This study investigates the optimal dwell point location of idle server within a multi–aisle automated storage and retrieval system. The objective function herein is to minimise the expected value of the next transaction time for the automated storage and retrieval system. After a brief review of the relevant literature on dwell point location, this research shows that the single server, multi–aisle dwell point location problem can be solved via an application of classical optimisation of a special class of Tchebychev expected distance functions.